Wonder, delusions and meaning. (August 2022) - Baldwin, Christopher Donald
Abstract : Summary: Strands of thought in the philosophy of mind offer another way of looking at the nature of mental illness and how it arises from intense emotional states. Analysing the phenomenon of wonder is suggested as a novel approach to explaining delusions and variations in insight.